Results of shared learning of a new magnetic seed localisation device – A UK iBRA-NET breast cancer localisation study. Issue 12 (December 2022) - Morgan, Jenna L.; Bromley, Hannah L.; Dave, Rajiv V.; Masannat, Yazan; Masudi, Tahir; Mylvaganam, Senthurun; Elgammal, Suzanne; Barnes, Nicola; Down, Sue; Holcombe, Chris; Potter, Shelley; Gardiner, Matthew D.; et al.
Abstract: Introduction: Shared learning is imperative in the assessment and safe implementation of new healthcare interventions. Magnetic seeds (Magseed®) potentially offer logistical benefit over wire localisation for non-palpable breast lesions but few data exist on outcomes comparing these techniques. A national registration study (iBRA-NET) was conducted to collate device outcomes. In order to share learning, thematic analysis was conducted to ascertain early clinical experiences of Magseed® and wire guided localisation and explore how learning events may be applied to improve clinical outcomes. Methods: A qualitative study of 27 oncoplastic surgeons, radiologists and physicians was conducted in January 2020 to ascertain the feasibility and challenges associated with Magseed® versus wire breast localisation surgery. Four focus groups were asked to discuss experiences, concerns and shared learning outcomes which were tabulated and analysed thematically. Results: Three key themes were identified comparing Magseed® and wire localisation of breast lesions relating to preoperative, intraoperative and postoperative learning outcomes. Percutaneous Magseed® detection, instrument interference and potential seed or wire dislodgement were the most common issues identified. Clinician experience suggested Magseed® index lesion identification was non-inferior to wire placement and improved the patient pathway in terms of scheduling and multi-site insertion. Conclusions: Prospective shared learning suggested Magseed® offered additional non-clinical benefits over wire localisation, improving the efficiency of the patient pathway. Recommendations for improving breast localisation technique, appropriate patient selection and clinical practice through shared learning are discussed that may aid other surgeons in the adoption of this relatively new technique.